Improving Educational Quality Based on Facilities, Infrastructure, and School Culture: Teacher Work Motivation as a Mediating Variable - A. Syarah; B. Herawan Hayadi; Mutoharoh Mutoharoh (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Improving primary education quality requires adequate facilities, a positive school culture, and strong teacher work motivation. This study examines the role of facilities and infrastructure and school culture in improving educational quality through teacher work motivation at SD Negeri Banjarwangi, Pandeglang Regency. A qualitative case study approach was employed with purposively selected informants, including the school principal, teachers, and school supervisor. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model through data reduction, data display, and conclusion drawing and verification. Data trustworthiness was ensured through source and technique triangulation and member checking. The findings reveal that basic educational facilities support learning activities, although limitations remain in digital facilities, instructional media, library resources, and supporting facilities. School culture is reflected in religious values, discipline, responsibility, cooperation, integrity, environmental awareness, and character-building practices. Teacher work motivation is influenced by intrinsic factors, such as professional responsibility and commitment, and extrinsic factors, including leadership support, a supportive work environment, appreciation, professional development opportunities, and available facilities. These factors encourage effective resource utilization, instructional creativity, and improved educational services. The study concludes that educational quality is enhanced through the synergy of facilities, school culture, and teacher motivation, with motivation functioning as a connecting mechanism. The study contributes a qualitative explanation of this integrative mechanism in a public primary school context.